2021
DOI: 10.1158/1078-0432.ccr-20-4009
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fusobacterium nucleatum with Specific T-cell Subsets in the Colorectal Carcinoma Microenvironment

Abstract: Purpose: While evidence indicates that Fusobacterium nucleatum (F. nucleatum) may promote colorectal carcinogenesis through its suppressive effect on T-cell-mediated antitumor immunity, the specific T-cell subsets involved remain uncertain.Experimental Design: We measured F. nucleatum DNA within tumor tissue by quantitative PCR on 933 cases (including 128 F. nucleatum-positive cases) among 4,465 incident colorectal carcinoma cases in two prospective cohorts. Multiplex immunofluorescence combined with digital i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 58 publications
1
31
0
Order By: Relevance
“…If the Megasphaera sp. XA511 translocated to the tumor microenvironment, the intra-tumor bacteria could play a role in either the differentiation or proliferation of multiple tumor-infiltrating immune cells thus affecting the anti-cancer immune responses ( 48 50 ). Besides, the microbiota-derived STING agonists can also induce IFN-I production through monocytes in tumors, thereby making the tumor microenvironment more conducive for immune response ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the Megasphaera sp. XA511 translocated to the tumor microenvironment, the intra-tumor bacteria could play a role in either the differentiation or proliferation of multiple tumor-infiltrating immune cells thus affecting the anti-cancer immune responses ( 48 50 ). Besides, the microbiota-derived STING agonists can also induce IFN-I production through monocytes in tumors, thereby making the tumor microenvironment more conducive for immune response ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…(3) Regarding its relationship with molecular features, intratumoral F. nucleatum is associated with high microsatellite instability, the CpG island methylator phenotype (CIMP) status, and certain gene mutations ( Tahara et al, 2014 ). In addition to the cancer cells, F. nucleatum is also associated with low CD3 + T cells ( Mima et al, 2015 ; Borowsky et al, 2021 ).…”
Section: F Nucleatum and Crc: Clinical Studies In Different Sample Typesmentioning
confidence: 99%
“…Epidemiological studies have revealed that a high abundance of F. nucleatum is associated with a low level of CD3 + T cells ( Mima et al, 2015 ), specifically CD3 + CD4 + CD45RO + cells ( Borowsky et al, 2021 ). This may be because F. nucleatum has a direct or indirect inhibitory effect on CD3 + T cells.…”
Section: The Mechanisms By Which F Nucleatum Is Involved In Various Crc Stagesmentioning
confidence: 99%
“…Each slide was then treated with a nuclear counterstain 14',6-diamidino-2-phenylindole (DAPI) (FP1490, PerkinElmer). 36 Digital images were acquired using a Vectra 3.0 quantitative pathology imaging system (PerkinElmer) equipped with a 20× objective. Large areas with necrosis, artefact, or excessive tissue folding were excluded from analysis.…”
Section: T-cell Multiplex Immunofluorescence Stainingmentioning
confidence: 99%